Proceedings from The Consortium for Technology & Innovation in Pediatrics (CTIP) 2024 Annual Pediatric Device Innovation Symposium - Tamara P. Lambert; Grzegorz Zapotoczny; Bianca Riello; Nadine Afari; Yaniv Bar-Cohen; Madison Christmas; Salima Jamal; Shahida Qazi; Melissa A. Bent; Juan Espinoza (BMC Proceedings)
Abstract On August 9, 2024, the CTIP symposium brought together various stakeholders in pediatric medical device (PMD) innovation to discuss the current state of pediatric medical devices (PMDs) and action steps that can collectively be taken to further drive PMD innovation. Meeting topics included 1) the Future of Pediatric Innovation, 2) Engaging Patients and Their Families in PMD Development, 3) Partnership Opportunities to Support PMD Research and Development (R&D), 4) Leveraging Real-World Evidence to Enhance PMDs, and 5) Fundraising and Investing in Pediatrics. This paper provides a comprehensive summary of the symposium proceedings, highlighting the critical needs, challenges, and opportunities in the PMD sector, and outlines potential areas for collaboration among stakeholders to drive progress in PMD development.